2013
DOI: 10.1017/s0950268812003111
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic patterns of cerebral malaria admissions in Papua New Guinea for the years 1987–1996

Abstract: Data on the dynamics of malaria incidence, admissions and mortality and their best possible description are very important to better forecast and assess the implementation of programmes to register, monitor (e.g. by remote sensing) and control the disease, especially in endemic zones. Semi-annual and seasonal cycles in malaria rates have been observed in various countries and close similarity with cycles in the natural environment (temperature, heliogeophysical activity, etc.), host immunity and/or virulence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…About 11-year (Horrebow-Schwabe) cycles of relative sunspot numbers [5][6][7] have also been reported to characterize communicable diseases such as malaria, as suggested earlier by Dimitrov et al [8]. In their analysis of cerebral malaria in Papua New Guinea (latitude between 0° and 12°S, longitude 140°-160°E), these authors also reported the presence of a strong calendar-yearly component, in the absence of a marked transyear.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…About 11-year (Horrebow-Schwabe) cycles of relative sunspot numbers [5][6][7] have also been reported to characterize communicable diseases such as malaria, as suggested earlier by Dimitrov et al [8]. In their analysis of cerebral malaria in Papua New Guinea (latitude between 0° and 12°S, longitude 140°-160°E), these authors also reported the presence of a strong calendar-yearly component, in the absence of a marked transyear.…”
Section: Introductionmentioning
confidence: 91%
“…Herein, we revisit published data on the incidence of malaria in different geographic locations near the equator. For this purpose, we turn to data in Papua New Guinea [8], Thailand, and Karuzi, Burundi [10], to explore any differences in terms of the relative prominence of transyears versus the calendar year. Our meta-analysis raises the question whether space weather may also contribute to communicable diseases like malaria in certain geographic…”
Section: Introductionmentioning
confidence: 99%
“…As a second step, autocorrelation and spectral functions for amplitude and density were explored to examine whether the variations may exhibit cyclic patterns (Figs 2, 3). Last, a periodogram regression analysis (PRA) with determination of the cycle length and its statistical significance at P < 0·05 was applied [5,[11][12][13][14]. PRA, using the sigma method for testing the statistical significance of the linear correlation coefficients, was successfully applied in earlier studies on helioepidemiology of various cancers and infectious diseases [5,[11][12][13].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Last, a periodogram regression analysis (PRA) with determination of the cycle length and its statistical significance at P < 0·05 was applied [5,[11][12][13][14]. PRA, using the sigma method for testing the statistical significance of the linear correlation coefficients, was successfully applied in earlier studies on helioepidemiology of various cancers and infectious diseases [5,[11][12][13]. In this work we approximated the studied time series f(t) with a number of minimizing correlation-regression functions F(t) of periodic mode:…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation